A METHOD FOR USER AUTHENTICATING TO CRITICAL INFRASTRUCTURE OBJECTS BASED ON VOICE MESSAGE IDENTIFICATION - Trysnyuk, Vasyl; Nagornyi, Yevhen; Smetanin, Kirill; Humeniuk, Igor; Uvarova, Tetyana (Сучасні інформаційні системи, 2020)
The subject of the research is the protection of critical infrastructure objects from unauthorized access based on voice message identification. The purpose of the research is to consider the main methods and algorithms for identifying an individual by voice, as well as the development of a software implementation of the restricted zone access control system, which allows improving the security of the standard password system by introducing voice authorization technologies and improving the algorithm for selecting voice fragments in audio files. Therefore, the purpose determines following tasks: analysis of the advantages and disadvantages of existing methods of information protection to infrastructure objects; determination of the optimal method of identification by voice message; a description of the main features of the implementation and use of Mel-frequency kastelnik coefficients (MFKC). Are used such methods: system approach, system analysis, theory of algorithms. The following results were obtained: an algorithm was developed for storing users ' voice data for further use in authorization, the voice authorization subsystem; the corresponding software of the computer system has been developed. Conclusions: based on the example of applying the biometric method of user authentication to critical infrastructure objects based on voice message identification, this method of user authentication should be used as an additional method of multi-factor authentication by entering an additional password or another method of biometric user authentication.